Effect of groove shape on the hydrodynamic lubrication of journal bearing considering cavitation. Issue 5 (10th January 2020) - Chen, Yu; Feng, Jun; Sun, Y.; Peng, Xu; Dai, Qiao; Yu, Chengtao
Abstract : Purpose: The purpose of this study is to investigate the influence of groove shape on the hydrodynamic characteristics of a journal bearing. Design/methodology/approach: The computational fluid dynamics model also takes into account the cavitation phenomena and thermal effect, which can illustrate the lubrication performance of a journal bearing. Findings: The hydrodynamic simulations of the journal bearing with the different groove shapes are conducted under different operation conditions. Originality/value: Based on the numerical analysis, the suggestions are presented for groove shape selection and can be used to the design of a journal bearing under the extreme operation condition.